Protection of national interests of Ukraine in the context of globalization - Martynenko, Valentyna Vitaliivna (Національний університет ДПС України, 2010)
This material is indicated the main tasks of state protection of Ukraine's national interests in the conditions of globalization.

У даному матеріалі визначено основні задачі державного захисту національних інтересів України в глобалізаційних умовах.
Keywords: globalization; national interests; national security; economic security; threats; глобалізація; національні інтереси; національна безпека; економічна безпека; загрози